Perancangan Sistem Informasi Akademis Perguruan Tinggi Berbasis Data DIKTI/EPSBED - Karto Iskandar; Reina Reina; Irma Irawati Ibrahim (Bina Nusantara University, 2011)
This research aims to help universities that do not have an academic information system and facilitate EPSBED data report to Directorate of Higher Education (DHE). The method used is the three first stages in the System Development Life Cycle (SDLC), which are systems engineering, requirements analysis, and design system. The result is a design of university business process, design of database, and design of user interface. This research finds that DHE has a specific data structure that can represent the basic activities of a study program. Therefore, this system design can be used for reporting of EPSBED data as well as for data collection of study program activities.